2016
DOI: 10.1007/s10964-016-0603-2
|View full text |Cite
|
Sign up to set email alerts
|

A Person-Centered Analysis of Risk Factors that Compromise Wellbeing in Emerging Adulthood

Abstract: The transition to adulthood is a major life course transition that can pose risk to wellbeing. Research is needed to identify patterns of risk for compromised wellbeing, in order to best identify supports for individuals during this potentially vulnerable transition. The purpose of this study was to identify profiles of risk in an emerging adulthood sample, and to relate these profiles to mental health and subjective and academic wellbeing. Undergraduate emerging adults (N = 903, 82 % female), aged 18-25 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 128 publications
(112 reference statements)
1
31
0
Order By: Relevance
“…From a mental health perspective, emerging adulthood-which includes the university years-has been considered a life course stage of elevated risk due to increased responsibilities and demands for self-direction [8][9][10], which contributes to changes in health or risk-taking and/or health-promoting behaviors [11]. Furthermore, emerging adulthood has been found to be a period where mental health problems peak [12][13][14][15], the prevalence of stress is high [16], and sleep disorders are common, the latter being a major risk factor for depression [17].…”
Section: Introductionmentioning
confidence: 99%
“…From a mental health perspective, emerging adulthood-which includes the university years-has been considered a life course stage of elevated risk due to increased responsibilities and demands for self-direction [8][9][10], which contributes to changes in health or risk-taking and/or health-promoting behaviors [11]. Furthermore, emerging adulthood has been found to be a period where mental health problems peak [12][13][14][15], the prevalence of stress is high [16], and sleep disorders are common, the latter being a major risk factor for depression [17].…”
Section: Introductionmentioning
confidence: 99%
“…Taking the distinction of affective dimensions, several studies have related them to aspects that are part of the psychological and emotional wellbeing of humans [5][6][7], such as life satisfaction, perfectionism or emotional intelligence, among others [8][9][10][11][12][13]. However, due to the fact that current research has identified that the associations of the TME do not consistently fit with all anxiety disorders and clinicians are working on improving the use of the model [14], the number of studies that analyze the relation between affect and social anxiety has increased during the last years.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, we observed that students with food insecurity are disproportionately launching their university careers with poorer mental health in addition to socioeconomic disadvantage. In our prior work, 38% to 50% of first-year students scored at or above clinical screening thresholds for depression 12 and risk for depression was greater for students with current financial stress 13 .…”
Section: Discussionmentioning
confidence: 79%